Promotional Video Design for Lembang Park and Zoo Educational Tour Packages for Elementary Schools in Bandung City - Purbasari, Sophia; Maulana, Daud Ramdan; Ferrari, R. Muhammad Luthfi (Sinergi International Journal of Communication Sciences, 2025)
Lembang Park and Zoo is an educational tourism destination that has experienced a decline in visitors due to the impact of the pandemic. To address this issue, Lembang Park and Zoo offers an educational tourism program directed at elementary school students. This program supports the elementary school curriculum and increases visitor numbers. However, the lack of promotion made it less known among teachers and parents of elementary schools in Bandung. Therefore, more effective promotional media are needed to attract the attention of teachers, parents, and students and increase visitor numbers. This study identifies elementary school teachers' and parents' needs and preferences and the effectiveness of promotional media through observation, interviews, questionnaires, and literature reviews. The promotional video for the Lembang Park and Zoo Educational Tour Package is designed to introduce the educational program to teachers and parents of elementary students in an informative, effective, and efficient manner. The video is designed to ensure teachers and parents can easily understand the information about educational tours and animal knowledge at Lembang Park and Zoo. This study increases visitor numbers from the elementary school group segment and meets the need for quick and efficient information.